Differences in Intersubject Early Readiness Potentials Between Voluntary and Instructed Actions - Zhang, Lipeng; Zhang, Rui; Yao, Dezhong; Shi, Li; Gao, Jinfeng; Hu, Yuxia (Frontiers in Psychology, 2020)
Abstract: The readiness potential (RP) is a slow negative EEG potential prior to voluntary action and was first described by Kornhuber and Deecke in 1965. Recent studies have demonstrated that a few subjects do not exhibit standard RP before voluntary action. In our previous study, we also found that some subjects did not show an early RP preceding instructed action. Although this phenomenon may be meaningful, no studies have yet investigated its origins. In the present study, we designed and implemented an experimental paradigm involving voluntary and instructed actions in the form of hand movements from 29 subjects with concurrent acquisition of electroencephalograms (EEGs). According to whether the subjects showed a standard RP waveform during instructed action, they were divided into the SHOW and NOSHOW group. Then, the RPs and voltage topographies were plotted for each group. Finally, the slope of each epoch at the early RP phase was estimated. We showed that early RPs were absent in 14 of 29 subjects during instructed actions. Besides, based on the slow cortical potential (SCP) sampling hypothesis, we also showed a decreased proportion in the negative potential for the NOSHOW group. Our results suggested that early RP is absent among approximately half of subjects during instructed action and the decreased proportion of negative potential shifts may account for the absence of the early RP in the NOSHOW group.